2012
DOI: 10.1111/j.1365-2826.2012.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways for High Voltage‐Activated Ca2+ Influx in Anterior Pituitary Lactotrophs and Somatotrophs

Abstract: The present study demonstrates that a significant proportion of high voltage-activated (HVA) Ca(2+) influx in native rat anterior pituitary cells is carried through non-L-type Ca(2+) channels. Using whole-cell patch-clamp recordings and specific Ca(2+) channel toxin blockers, we show that approximately 35% of the HVA Ca(2+) influx in somatotrophs and lactotrophs is carried through Ca(v) 2.1, Ca(v) 2.2 and Ca(v) 2.3 channels, and that somatotrophs and lactotrophs share similar proportions of these non-L-type Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…We recently identified multiple Ca 2+ channel α1 subunits in the membranes of AP cells, including L‐type (Ca v 1.2, Ca v 1.3), P/Q‐type (Ca v 2.1), N‐type (Ca v 2.2) and R‐type (Ca v 2.3) channels. We also demonstrated that a substantial fraction (approximately 46%) of the VGCI in AP cells is carried through non‐L‐type Ca 2+ channels (P/Q‐, N‐ and R‐type channels) . Additionally, via flotation experiments, we demonstrated that these multiple pathways for VGCI in AP cells are segregated among raft and nonraft membrane compartments .…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…We recently identified multiple Ca 2+ channel α1 subunits in the membranes of AP cells, including L‐type (Ca v 1.2, Ca v 1.3), P/Q‐type (Ca v 2.1), N‐type (Ca v 2.2) and R‐type (Ca v 2.3) channels. We also demonstrated that a substantial fraction (approximately 46%) of the VGCI in AP cells is carried through non‐L‐type Ca 2+ channels (P/Q‐, N‐ and R‐type channels) . Additionally, via flotation experiments, we demonstrated that these multiple pathways for VGCI in AP cells are segregated among raft and nonraft membrane compartments .…”
mentioning
confidence: 62%
“…We also demonstrated that a substantial fraction (approximately 46%) of the VGCI in AP cells is carried through non‐L‐type Ca 2+ channels (P/Q‐, N‐ and R‐type channels) . Additionally, via flotation experiments, we demonstrated that these multiple pathways for VGCI in AP cells are segregated among raft and nonraft membrane compartments . In the present study, we examined the relative contribution of L‐type and non‐L‐type VGCI to GH secretion.…”
mentioning
confidence: 79%
See 3 more Smart Citations